2018
DOI: 10.1039/c7an01800b
|View full text |Cite
|
Sign up to set email alerts
|

Spectrochemical analyses of growth phase-related bacterial responses to low (environmentally-relevant) concentrations of tetracycline and nanoparticulate silver

Abstract: Exposure to environmental insults generally occurs at low levels, making it challenging to measure bacterial responses to such interactions. Additionally, microbial behaviour and phenotype varies in differing bacterial types or growth phases, likely giving rise to growth- or species-specific responses to environmental stimuli. The present study applied a spectrochemical tool, infrared (IR) spectral interrogation coupled with multivariate analysis, to investigate the growth- and species-specific responses of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…− stretching in nucleic acids and ring bases as well as changes in the lipids, fatty acids and proteins have been reported. [31,32] The biomolecular changes observed with rifampicin were also in line with its mode of action. It is important to mention that the bactericidal or static activity of rifampicin is organism specific [33].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…− stretching in nucleic acids and ring bases as well as changes in the lipids, fatty acids and proteins have been reported. [31,32] The biomolecular changes observed with rifampicin were also in line with its mode of action. It is important to mention that the bactericidal or static activity of rifampicin is organism specific [33].…”
Section: Discussionmentioning
confidence: 82%
“…In future, it will be important to correlate our findings with nutrient depletion and starvation observed in the environment. It has been shown that long-term exposure to antimicrobials often drives bacterial cells into dormant states or causes them to display additional cellular components like fatty acids, resulting in a broader range of spectral modifications compared with short-term exposure [31,32]. It is also necessary to evaluate our Raman markers with a host of other bacterial strains and/or panel of clinically-relevant antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivated with carbohydrate, for instance, biospectra of S. chinense QD10 have specific biomarkers including PO 2 asymmetric (~ 1265 cm -1 ), RNA (~ 1117 cm -1 ), CH in-plane bend (~ 1510 cm -1 ), Amide I (~ 1659 cm -1 ) and C=O, lipids (~ 1740 cm -1 ), indicating the occurrence of complex carbohydrate metabolic processes during fungal growth (Figure 4). These biomarkers are significantly different from those linked with bacterial growth except for Amide I (~ 1659 cm -1 ) (Jin et al, 2018a;Jin et al, 2018b), suggesting distinct metabolite profiles between fungal and bacterial growth. Carbohydrates are reported to associate with fungal metabolism, not only providing energy for the synthesis of trehalose, polyols, glycogen, fatty acids and other cellular components, but also supplying carbon skeleton for other metabolic processes, such as hyphal growth and amino acid biosynthesis (Bago et al, 2003;Deveau et al, 2008;Rasmussen et al, 2008).…”
Section: Spectral Biomarkers For S Chinense Qd10 Growth Across Carbon Source Groupsmentioning
confidence: 75%
“…The IR bands significantly correlated with GI include 1340 cm -1 (collagen), 1136 cm -1 (collagen) and 966 cm -1 (C-C DNA, Figure 5B-5D), implying strong associations of these cellular components with fungal growth. Among them, the DNA-spectral biomarker represents DNA replication through cell reproduction process (Jin et al, 2018a;Jin et al, 2018b). Additionally, the collagen-associated spectral alterations are very likely linked to the formation of fungal fimbriae, which consist of collagen and are abundant on extracochlear surfaces (Celerin et al, 1996).…”
Section: Spectral Biomarkers For S Chinense Qd10 Growth Across Carbon Source Groupsmentioning
confidence: 99%